P212 Should intercostal tube drainage be the first intervention in the management of primary spontaneous pneumothorax with complete lung collapse?. (14th November 2013) - Ganaie, MB; Bikmalla, S; Khalil, MA; Afridi, MA; Haris, M; Hussain, IR
Abstract : Introduction and Objectives: Primary Spontaneous Pneumothorax (PSP) is a common presentation with significant variation in severity and treatment strategies globally. There is no differentiation between 'large' PSP with complete lung collapse and 'large pneumothorax' in the current treatment algorithms. Previous studies comparing needle aspiration (NA) and intercostal tube (ICT) drainage for all PSP requiring intervention have shown no significant difference in immediate success rate, early failure rate and length of stay. We aimed to compare NA with ICT as the first intervention in those with complete lung collapse. Methods: Retrospective, observational study of 212 consecutive pneumothorax episodes between January 2012 and December 2012. Those with secondary spontaneous pneumothorax (SSP), history of trauma and iatrogenic pneumothorax were excluded. Pneumothorax with no visible aerated ipsilateral lung on plain chest radiograph was defined as 'complete lung collapse'. Patient records and plain chest radiographs on PACS were reviewed and data was analysed. Values of p < 0.05 were considered statistically significant. Results: Of the 212 episodes, 51 (33%) were PSP. Median age was 29 years (IQR 22–38); male 33(75%), female 18(25%). 5(1%) were observed; 28(55%) had NA and 18(36%) had ICT as 1 st intervention. NA was successful in 13(46%) which is comparable to previous studies. 33(65%) required hospitalisation and median length of stay (LOS) for all PSP was 4 days. 18(35%) required definitive surgical intervention. Conclusion: Our results show significantly better lung re-inflation rates with ICT as the first intervention in the management of PSP with complete lung collapse and there was no added benefit in performing NA. We propose a further sub-group of PSP with complete lung collapse in which NA should not be attempted, however well-designed prospective studies are required to validate this.